Who Was Nehemiah ben Hacaliah? - Lisbeth S. Fried (Journal of Hebrew Scriptures, 2022)
The article argues for the identification of three separate protagonists in the book of Nehemiah. The first is an unnamed wine steward who was appointed to rebuild Jerusalem’s city wall in the twentieth year of Artaxerxes I. The second is a governor of Judah, who was appointed to that role in the same year. According to what may be his actual seal, however, this governor’s name is Yehoʿezer, not Nehemiah. A third protagonist was the head of the temple priesthood, but at the time of the temple’s dedication in 516, not during the reign of any Artaxerxes. Only he was called Nehemiah, however, his full name being Nehemiah Attršiātā ben Hacaliah.